Penghindaran Pajak dan Nilai Perusahaan: Modal Intelektual Sebagai Pemoderasi - Khaled, Januar; Abbas, Yulianti (Politeknik Ganesha Medan, 2024)
Each company will evaluate the performance that has been carried out using company value as an indicator. Company value is the real value that comes from the investor's perspective which relates the company to the share price. The aim of this research is to analyze the relationship between tax avoidance and company value, and the moderating influence of intellectual capital on the relationship between tax avoidance and company value. The data used in this research are all companies listed on the IDX in 2018-2022. The research sample after purposive sampling was carried out was 175 companies. This research uses unbalanced panel data, so the total data sample is 627. The research results show that tax avoidance is negatively related to company value and intellectual capital cannot moderate the relationship between tax avoidance and company value. The conclusion of this research is to prove that tax avoidance has a negative effect on company value, so that if a company engages in tax avoidance behavior it will reduce the value of the company related to agency problems, and this research explains that when intellectual capital is used as a moderator it shows results that are not related to company value. , this explains that the company's intellectual capital has no effect when there is a agency problem.